Pengaruh Kepemimpinan Transformasional, Extrinsic Reward, dan Kesejahteraan Karyawan terhadap Kepuasan Kerja Karyawan KSPPS BMT Dana Insani Gunungkidul - Ramdani, Ica; Subiyanto, Didik; Kirana, Kusuma Chandra (Jurnal Maksipreneur, 2024)
The purpose of this research is to determine the influence of transformational leadership, extrinsic rewards, and employee welfare on job satisfaction. The population used was all employees from the KSPPS BMT Dana Insani Gunungkidul head office totaling 38 employees. Saturated sampling is used as a sampling technique and quantitative method, carried out by collecting data by distributing questionnaires using Google Forms directly. Data analysis processing was carried out using SPSS Version 20 to determine the hypothesis results using multiple linear regression analysis and supported by t-test hypothesis testing. The results of this research show that transformational leadership has a positive and significant effect on job satisfaction, while extrinsic rewards do not have a significant effect on job satisfaction. Apart from that, it was also found that employee welfare had a positive and significant effect on job satisfaction.